Osteoarthritis with depression: mapping publication status and exploring hotspots - Zhang, Meng; Li, Hao; Li, Qingshan; Yang, Zhen; Deng, Haobin; Xu, Yingying; Guo, Quanyi (Frontiers in Psychology, 2024)
Depression is a common psychological complication in osteoarthritis (OA) patients, and its incidence gets more and more attention year by year worldwide. This study investigates the association between OA and depression through a bibliometric analysis of published studies. It aims to identify leading authors, institutions, and countries to highlight research hotspots and suggest potential future directions. We collected publications on OA and depression from 1994 to 2024 using the Web of Science Core Collection (WOSCC) database. Bibliographic information, including authorship, country of origin, citation frequency, and visualizations, was generated using VOSviewer, R software, and CiteSpace. A total of 2,342 articles were identified. The United States led in publications with 906 articles, Boston University was the most prolific institution with 56 publications, BMC Musculoskeletal Disorders was the top journal with 71 publications, and Stefania Maggi was the most productive author with 19 publications. The primary research hotspots identified were: “The relationship between depression and OA,” “Disability and prevalence,” and “Characteristics of older people suffering depression after OA.” Predicted future research frontiers include: “Treating depression in OA patients with multimorbidity,” “Psychometric properties of instruments for assessing depression and anxiety in OA patients,” “Depression or anxiety in patients with surgical intervention,” and “Other mental diseases in OA patients.” This bibliometric analysis underscores the importance of understanding the link between OA and depressive disorders, potentially guiding new research directions.